PEMUDA NU DALAM PUSARAN WACANA ANTI KOMUNISME: Sebuah Pergolakan Ideologi - Siddiq, Imamul Huda Al; Widianto, Ahmad Arif (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
The role of the NU youth as an extension of the NU kyai was so great in eradicating parties and forbidden ideologies such as the PKI. Based on the basic principles of NahdlatulUlama such as tawasuth, tawazun, i’tidal, and tasamuh, plus a platform for thinking and acting based on the principles of the ushulfiqh and guidance from kyai, NU youths steadfastly declared war with communism. Similarly, when they defend the rights of former Communist activists or those who are considered Communists and their families, they are also based on these principles. For this reason, this paper aims to examine the idealized upheaval of NU youth in addressing the anti-communism discourse.This article was written by critically examining pre-existing scientific texts to expose ideological upheaval among NU youth sociologically. In simple terms, through this article it can be concluded that NU youth based on existing principles have a big contribution in maintaining the integrity of the Republic of Indonesia, starting from the eradication of the PKI, as well as other efforts to defend Indonesia. On the other hand, they also have concern for oppressed groups including former 1965 political prisoners and their families. They were so diligent in fighting for the rights of former political prisoners in 1965 even though in the past they had also suppressed the PKI to its roots. One of the discourses that arose relating to the anti-communism discourse was the discourse of reconciliation between the NU group and Communism. The discourse was responded to differently by NU youth. Some consider it a form of humanism, and there are those who see it as a bad idea, and some even consider it as an extreme step.Peran pemuda NU sebagai kepanjangan tangan dari para kyai NU begitu besar dalam pemberantasan partai dan ideologi terlarang seperti PKI. Dengan berpijak pada prinsip dasar Nahdlatul Ulama seperti tawasuth, tawazun, i’tidal, dan tasamuh, ditambah pijakan berpikir dan bertindak yang didasarkan pada prinsip-prinsip yang ada pada ushul fiqh serta petunjuk dari para kyai, pemuda NU dengan mantap menyatakan perang dengan komunisme. Begitu pula ketika mereka membela hak-hak dari mantan aktivis Komunis atau yang dianggap Komunis dan keluarganya, mereka pun juga berdasar pada prinsip-prinsip tersebut. Untuk itu tulisan ini bertujuan untuk mengkaji pergolakan idelogi di kalangan pemuda NU dalam menyikapi wacana anti-komunisme.Artikel ini ditulis dengan menelaah secara kritis teks-teks ilmiah yang telah ada sebelumnya untuk menelanjangi pergolakan ideologi di kalangan pemuda NU secara sosiologis. Secara sederhana, melalui artikel ini dapat disimpulkan bahwa pemuda NU dengan berdasar prinsip yang ada memiliki andil besar dalam mempertahankan keutuhan NKRI, mulai dari pemberantasan PKI, serta upaya-upaya lain dalam mempertahankan Indonesia. Di sisi lain, mereka juga memiliki perhatian terhadap kelompok tertindas termasuk mantan tahanan politik 1965 dan keluarganya. Mereka begitu gigih memperjuangkan hak-hak mantan tahanan politik 1965 meski di masa lalu mereka pula yang memberangus PKI sampai ke akarnya. Salah satu wacana yang mengemuka berkaitan dengan wacana anti-komunisme adalah wacana rekonsiliasi antara golongan NU dan Komunisme. Wacana tersebut ditanggapi berbeda-beda oleh pemuda NU. Ada yang menganggapnya sebagai bentuk sifat humanis, adapula yang melihatnya sebagai gagasan buruk, bahkan ada yang memandang rekonsiliasi tersebut sebagai langkah ekstrim.